Relationship Between Nutritional Status and Anemia Incidence in Pregnant Women in the Second Trimester : (In the Work Area of Hikun Health Center Tabalong Regency, South Kalimantan) - Dewi Wulandari; Anik Purwati; Maria Veronika Widiatrilupi (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2025)
It is crucial for individuals at all life stages—ranging from fetuses to the elderly—to receive proper nutrition for healthy development and well-being. During pregnancy, malnutrition can lead to abnormal physical development, impaired cognitive function, decreased work productivity, reduced immune resistance, and, ultimately, higher risks of illness and death. Women who maintain proper nutritional intake before conception can help prevent anemia, as the increased demand for iron during pregnancy may otherwise lead to deficiencies. This study aims to analyze the relationship between individual nutritional conditions and the prevalence of anemia in pregnant women during their second trimester in the work area of the Hikun Health Center, Tabalong Regency, South Kalimantan. The research utilized an observational analytical approach with a cross-sectional design. Univariate and bivariate analyses were conducted, where univariate analysis examined the distribution of individual variables, and bivariate analysis employed the chi-square method to assess the relationship between two variables. The findings indicated that non-ideal nutritional status was associated with a decrease in anemia cases by 80.0%. However, this association was not statistically significant (p-value = 0.317). The data analysis concluded that there was no significant effect between maternal nutrition and anemia levels in pregnant women at the Hikun Health Center. These results suggest that while nutritional status is a factor in anemia prevalence, other variables may also play a role, and further research is needed to explore potential contributing factors and to refine the understanding of how nutrition, dietary habits, and lifestyle choices impact anemia in pregnant women.